2015
DOI: 10.1039/c5dt02349a
|View full text |Cite
|
Sign up to set email alerts
|

Electron deficient nonplanar β-octachlorovanadylporphyrin as a highly efficient and selective epoxidation catalyst for olefins

Abstract: We have synthesized 2,3,7,8,12,13,17,18-octachloro-meso-tetraphenylporphyrinatooxidovanadium(iv) (VOTPPCl8) and characterized by various spectroscopic (UV-Vis, IR and EPR) techniques, MALDI-TOF mass spectrometry and elemental analysis. The DFT optimized structure of VOTPPCl8 in CH3CN exhibited a highly nonplanar saddle shape conformation of the porphyrin macrocycle. The cyclic voltammogram of VOTPPCl8 showed a 500 mV anodic shift in the first ring reduction potential and 220 mV in the first ring oxidation pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 88 publications
(23 reference statements)
2
27
0
Order By: Relevance
“…From the anisotropic EPR spectrum of 2 the g ∥ and g ⊥ were depicted as 1.959 and 1.987, respectively, whereas A ∥ and A ⊥ were obtained as 167.1 × 10 −4 and 74.4 × 10 −4 cm −1 , respectively. All these values are within the permissible range for an axially compressed V(IV) d 1 system [16,18,26,27] …”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…From the anisotropic EPR spectrum of 2 the g ∥ and g ⊥ were depicted as 1.959 and 1.987, respectively, whereas A ∥ and A ⊥ were obtained as 167.1 × 10 −4 and 74.4 × 10 −4 cm −1 , respectively. All these values are within the permissible range for an axially compressed V(IV) d 1 system [16,18,26,27] …”
Section: Resultsmentioning
confidence: 53%
“…Figure 6 presents cyclic voltammograms ( vs . Ag/AgCl) of 1 and 2 in CH 2 Cl 2 containing 0.1 M TBAPF 6 at 298 K. In general, porphyrins show two reversible oxidations and reductions during cyclic voltammetric studies [16,18,28–31] . Similarly, 1 and 2 show two reversible porphyrin ring‐centred one electron oxidations and reductions [30] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[52][53][54] We have earlier reported the catalytic efficacy of an b-octachlorovanadylporphyrin complex towards alkene epoxidation. 55 In continuity of our efforts to develop versatile catalysts for alkene epoxidation, we hereby report the facile synthesis, characterization, spectral properties, X-ray structure and catalytic applications of vanadyl tetrabromoporphyrin VOTPPBr 4 (1). We have also observed that steric (bulky) and electron withdrawing factors play a major role in determining the efficiency of the catalysts for epoxidizing alkenes.…”
Section: Introductionmentioning
confidence: 90%
“…1). 55,57 Different spectrometric techniques like UV-visible, FTIR, MALDI-TOF-MS, EPR and single crystal XRD were used to characterize the target compound 1. The UV-visible spectrum of 1 in CH 2 Cl 2 is shown in Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%